2015
DOI: 10.1515/mmcks-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

What is materialism? Testing two dominant perspectives on materialism in the marketing literature

Abstract: Abstract. Materialism is defined as the importance an individual attaches to worldly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…The individuals that hold a high level of materialistic attitude prefer the ownership of the products and thereby place the ownership of the products at the centre of their lives. Materialism is also found to be a major constraint in the sustainable development (Manchiraju & Krizan, 2015). Akbar et al (2016) found that materialism’s sub-dimension ‘possessiveness’ was the major barrier of sharing.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…The individuals that hold a high level of materialistic attitude prefer the ownership of the products and thereby place the ownership of the products at the centre of their lives. Materialism is also found to be a major constraint in the sustainable development (Manchiraju & Krizan, 2015). Akbar et al (2016) found that materialism’s sub-dimension ‘possessiveness’ was the major barrier of sharing.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…) Ahuvia ve Wong (2002). veManchiraju ve Krizan (2015) yaptıkları çalışmalarda kişilik özellikleri ile materyalizm arasındaki ilişkiyi tanımlamışlardır.Donnelly vd. (2012) ise çalışmasında beş faktör kişilik özelliklerinin materyalizm üzerinde etkili olduğunu belirtmiştir.…”
unclassified